2019
DOI: 10.3390/ijms20174136
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Mechanisms of Cisplatin Resistance: From Tumor Cell to Microenvironment

Abstract: Although cisplatin has been a pivotal chemotherapy drug in treating patients with various types of cancer for decades, drug resistance has been a major clinical impediment. In general, cisplatin exerts cytotoxic effects in tumor cells mainly through the generation of DNA-platinum adducts and subsequent DNA damage response. Accordingly, considerable effort has been devoted to clarify the resistance mechanisms inside tumor cells, such as decreased drug accumulation, enhanced detoxification activity, promotion of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
227
0
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(231 citation statements)
references
References 105 publications
0
227
0
4
Order By: Relevance
“…Furthermore, recurrence of ovarian cancer is up to 75% and the recurrent cancer can result in the acquisition of cisplatin resistance, as well [ 43 ]. Thus, cisplatin resistance is a limitation of cisplatin chemotherapy, since there are several molecular mechanisms leading to cisplatin resistance [ 45 , 46 , 47 ]. Among the mechanical reasons, previous studies showed that upregulation of FOXM1 induced cisplatin resistance in several cancer cells [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recurrence of ovarian cancer is up to 75% and the recurrent cancer can result in the acquisition of cisplatin resistance, as well [ 43 ]. Thus, cisplatin resistance is a limitation of cisplatin chemotherapy, since there are several molecular mechanisms leading to cisplatin resistance [ 45 , 46 , 47 ]. Among the mechanical reasons, previous studies showed that upregulation of FOXM1 induced cisplatin resistance in several cancer cells [ 48 , 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…The appearance of drug resistances, issuing from acquired or intrinsic multiple genetic and epigenetic changes, has also limited the clinical use of platinum-derived drugs [ 8 ]. Platinum-based treatment efficiency is challenged by cross-resistance and multiple changes including a decreased accumulation of the drug, a reduction in DNA–drug adducts, a modification in cell survival gene expression, an alteration of DNA damage repair mechanisms, modifications of transporters, protein trafficking, and altered cell metabolism [ 9 , 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…A decreased expression of the membrane copper transporter CTR1 or the organic cation transporter OCT2, as well as a high expression of the copper-exporting P-type ATPases, ATP7A and ATP7B, or the ATP-binding cassette multidrug transporter, MRP2, could lead to decreased intracellular levels of platinum drugs, thereby causing resistance. Furthermore, high expression levels of glutathione S-transferase, a detoxifying enzyme responsible for the formation of platinum-glutathione conjugates, would also facilitate resistance [52]. A combination of these already identified markers with differences in estrogen metabolism could allow a better prediction of platinum resistance in patients.…”
Section: Discussionmentioning
confidence: 99%